Identification of Four Secreted Aspartic Protease-Like Proteins Associated With Sophorolipids Synthesis in Starmerella bombicola CGMCC 1576 - Liu, Jun; Zhao, Guoqin; Zhang, Xinyu; Song, Xin (Frontiers in Microbiology, 2021)
The non-pathogenic yeast Starmerella bombicola CGMCC 1576 is an efficient producer of sophorolipids (SLs). The lactonic SLs are mainly produced with yeast extract and the acidic SLs are mainly produced with ammonium sulfate. Naturally produced SLs are a mixture of various lactonic and acidic SLs. Usually, the SL mixture are not well separated technically, and the separation cost is relatively high. In order to reduce the cost of separation, four secreted aspartic protease-like proteins were identified through proteomic analysis of fermentation broth of S. bombicola under different nitrogen source conditions. The coding genes of the four proteins, named sapl1, sapl2, sapl3 and sapl4, are of high sequence similarity (above 55%) and included in a gene cluster. The expression of the four genes was significantly up-regulated on (NH4)2SO4 compared with those on yeast extract. The four genes were deleted together to generate a strain ∆sapl. The titer of SLs in ∆sapl reached 60.71 g/L after 5 days’ fermentation using (NH4)2SO4 as the N-source, increased by 90% compared to the wild-type strain. The concentration of acidic SLs was 55.84 g/L, accounting for 92% of the total SLs. The yield of SLs from glucose (g/g) by Δsapl was 0.78, much higher than that by wild-type strain (0.47). However, no increase of SLs production was observed in Δsapl under yeast extract condition. Compared with that of the wild-type strain, the expression levels of the key genes for SLs synthesis were all up-regulated to varying degrees in ∆sapl under (NH4)2SO4 conditions and particularly the expression level of ugta1 encoding UDP glucosyltransferase was up-regulated by 14.3-folds. The results suggest that the sapl gene cluster is negatively involved in the production of SLs in the case of (NH4)2SO4 by restraining the expression of the key genes involved in SLs synthesis. The ∆sapl strain is an excellent producer of high-titer and high-yield acidic SLs.